Postponement of Marriage due to Inability to Read the Qur'an in Community Traditions Perspective of Munakahat Fiqh and Maslahah Murlah - Khuzaifah Khuzaifah; Izzul Mutho` (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The tradition of requiring the ability to read the Qur’an for prospective brides and grooms in Lambu District, Bima Regency, represents a living socio-religious practice with strong normative influence in the marriage process. In practice, this tradition may lead to the postponement of the marriage contract for individuals who have not yet met the required level of Qur’anic literacy. This study aims to analyze the legal status of the Qur’an-reading tradition from the perspective of Islamic marriage jurisprudence (fiqh munakahat) and to assess its relevance through the approaches of maslaḥah mursalah and ‘urf. This research employs a qualitative method with a juridical-sociological approach. Data were collected through interviews, observation, and documentation, and analyzed using descriptive-analytical techniques. The findings indicate that the ability to read the Qur’an is neither a pillar nor a legal requirement for the validity of marriage according to classical fiqh and the Compilation of Islamic Law. Nevertheless, this tradition may be categorized as valid custom (‘urf sahīh) because it does not contradict Islamic legal texts and serves to strengthen religious values within marriage. From the perspective of maslaḥah mursalah, the tradition contains clear benefits, particularly in the form of premarital religious guidance and the enhancement of moral readiness among prospective spouses. Therefore, the Qur’an-reading tradition should be maintained as a form of religious guidance, provided that it is not positioned as a mandatory legal requirement for the validity of marriage.